Symplastic glomus tumor of the urinary bladder treated by robot-assisted partial cystectomy: a case report and literature review. Issue 3 (August 2018) - Palmisano, Franco; Gadda, Franco; Spinelli, Matteo G.; Maggioni, Marco; Rocco, Bernardo; Montanari, Emanuele
Glomus tumors arising in the urinary bladder are extremely rare, and only two cases have been reported in the English Literature. We present a case of a 58-year-old man with an asymptomatic mass of the anterior wall of the bladder that measured 2.5 × 2.5 cm. Endoscopic excision was performed, and the tumor was diagnosed as symplastic glomus tumor. The patient finally underwent robotic-assisted partial cystectomy, and he remains healthy without any recurrence to date. After reviewing this case and previous reports, we analyzed the clinicopathologic features and treatment options for this rare neoplasm.